Metaphor and conceptual power approaches in international relations (Journal of Imam Al-Kadhim College, 2024)
Power phenomena has attached to the war phenomena along the history and its central rule which it plays in the field of the international relations, but the change in the international system environment consistently led to the change in the war nature and its function. In the 21th century, the countries looked forward to dominate or to withdraw of it. As a result, to change the concept and what is the power and what is it function in the international relations. Because of that dilemmas philosophy of the concepts in the international relations initially consider as linguistics and ideological problems. These dilemmas reflected on the form and the contents of the power definitions. So, because of the ambiguity is the fundamental characteristic of the power phenomena which is reflected on the understanding of the international relations until it became to get rid of the ambiguity is a necessity rather than a need. The ambiguity which surrounds the power phenomena is come from its international nature, in another words, it isn’t confined on solo society and culture. As an aim to get rid of this ambiguity the researchers adopted the linguistics metaphor to clarify and simplify its meanings, but that increased its ambiguity when these clarification among the societies with different languages which make it vary conceptual approaches as a natural result.